Отражение радоновых аномалий в магнитном поле и тектонических элементах Беларуси - Гарецкий, Р.Г.; Каратаев, Г.И.; Матвеев, А.В. (Геофизический журнал, 2016)
Regularities connecting radon anomalies in soil air of cover deposits of different genesis with magnetic anomalies and tectonic elements of Belarus have been indirectly determined through genetic types of Quaternary deposits. It is noted that the intensity of radon anomalies increases with transition to the tectonic structures subjected to multi-step processes of activation. Linearly stretched radon anomalies correlate with the deep faults of lithosphere. Опосередковано через генетичні типи четвертинних відкладів встановлено закономірності, що пов'язують радонові аномалії в ґрунтовому повітрі покривних відкладів різного генезису з магнітними аномаліями і тектонічними &\ементами Білорусі. Помічено, що інтенсивність радонових аномалій збільшується при переході до тектонічних структур, які витримали багатоетапні процеси активізації. Лінійно витягнуті аномалії корелюють з глибинними розломами літосфери.